2022
DOI: 10.1039/d2nj04297e
|View full text |Cite
|
Sign up to set email alerts
|

Constructing trifunctional MoTe2/As van der Waals heterostructures for versatile energy applications

Abstract: With the rapid expansion of material application, the limitation of single layer material has become more apparent and its intrinsic properties can no longer satisfy the growing demand. Construction of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…These phenomena include the mutual conversion between the indirect band gap and the direct band gap, the expansion of the band gap and the matching of the band gap with the visible and near-infrared regions. [7][8][9][10] In this work, a methodical investigation into the geometric structure, electronic properties, photocatalytic performance and optical properties of the Ag 2 Se monolayer under biaxial strain were carried out using density functional theory (DFT) computations. The current study found that the band arrangement of the Ag 2 Se monolayer straddles the HER and OER, and these barriers could be adjusted with strain.…”
Section: Introductionmentioning
confidence: 99%
“…These phenomena include the mutual conversion between the indirect band gap and the direct band gap, the expansion of the band gap and the matching of the band gap with the visible and near-infrared regions. [7][8][9][10] In this work, a methodical investigation into the geometric structure, electronic properties, photocatalytic performance and optical properties of the Ag 2 Se monolayer under biaxial strain were carried out using density functional theory (DFT) computations. The current study found that the band arrangement of the Ag 2 Se monolayer straddles the HER and OER, and these barriers could be adjusted with strain.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 To rationally build a heterostructure for global solar water splitting, three fundamental rules must be considered: (i) the sun can be utilized advantageously, (ii) the band edges are properly oriented with respect to the redox potentials of water, and (iii) slower electron−hole pair recombination and subsequent separation of photogenerated carriers. Several 2D heterostructures 12,13 have been presented thus far as catalysts for photocatalytic water splitting. It remains difficult to create a suitable photocatalyst with high activity and stability for hydrogen production despite experimental and theoretical efforts to do so.…”
Section: Introductionmentioning
confidence: 99%
“…Several 2D heterostructures , have been presented thus far as catalysts for photocatalytic water splitting. It remains difficult to create a suitable photocatalyst with high activity and stability for hydrogen production despite experimental and theoretical efforts to do so.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation